Lithium oxygen battery and preparation method thereof

By using porous composite oxygen electrodes in lithium oxygen batteries, using ZIF67-AgNWs doped skeleton material to provide high specific surface area and uniform pores, catalyze the O2 conversion reaction and decompose lithium peroxide, the problem of poor circulation performance of lithium oxygen batteries is solved, and the problem of lithium oxygen batteries is achieved. High capacity and long cycle life battery performance.

CN119208847APending Publication Date: 2024-12-27BEIFANG UNIV OF NATITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411289044.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Lithium oxygen batteries have problems such as poor circulation performance, low power capacity and unsatisfactory rate performance. This is mainly due to the deposition of solid product Li2O2 and its by-products in the cathode surface and pores, which hinders the diffusion path of Li+ and O2, resulting in slow reaction kinetics. .

Method used

Using porous composite oxygen electrodes, containing ZIF67-AgNWs doped skeleton material, provides uniform pores with high specific surface area and adjustable chemical environment, used to catalyze O2 conversion reactions, and decompose lithium peroxide during charging to avoid lithium carbonate Generate, improve cycle performance.

Benefits of technology

The long cycle life and high capacity of lithium oxygen batteries are achieved, the problem of poor cycle performance is overcome, the discharge capacity and charging efficiency of the battery are improved, the positive electrode surface polarization is avoided, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208847A_ABST
    Figure CN119208847A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium oxygen battery and a preparation method thereof, the battery comprises a porous composite oxygen electrode, a negative electrode, an electrolyte and a diaphragm, and the lithium oxygen battery is filled with oxygen or mixed gas containing oxygen; the porous composite oxygen electrode comprises a ZIF67-AgNWs doped framework material and a binding agent, and an internal pore channel used for being completely or partially filled with oxygen is formed in the porous composite oxygen electrode. The negative electrode is a lithium sheet; the electrolyte is an organic electrolyte formed by dissolving a lithium salt in an anhydrous ether solvent or an ionic liquid solvent; the diaphragm is a glass fiber diaphragm. The ZIF67-AgNWs doped framework material is applied to the lithium oxygen battery, so that the discharge capacity of the battery is increased; and the ZIF67-AgNWs doped framework material not only can store lithium ion contribution capacity, but also can catalyze generation and decomposition of a lithium-oxygen battery product lithium peroxide by using metal active sites in pores of the porous metal framework in a charging process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, in particular to a lithium oxygen battery and a preparation method thereof. Background Art

[0002] With the rapid development of the world economy, human beings are more dependent on sustainable energy. Most of the energy used in the current society is fossil energy, which is a non-renewable energy source. In today's fast-developing world, resources determine the speed of development, so sustainable resources are more needed. In order to meet this demand, a reliable renewable energy system must be built. At present, renewable energy sources include solar energy, tidal energy, wind energy and geothermal energy. Researchers from all over the world are committed to developing effective sustainable renewable energy to replace fossil energy, so as to achieve the goal of sustainable development in a real sense. To match renewable energy, it is necessary to develop energy storage, among which lithium-ion batteries, which are the most mature in commercialization, have become an important means of electrochemical energy storage. Rechargeable lithium-ion batteries provide great convenience for people in all aspects, especially in portable electronic devices, battery-powered electric vehicles and energy storage. However, the energy density of lithium-ion batteries has a bottleneck, and the accompanying safety and other issues have limited its widespread promotion in the fields of new energy vehicles and smart grids.

[0003] Lithium-oxygen batteries have a high theoretical energy density (3500Wh kg -1 , based on the positive electrode reaction: O2+2Li + +2e - →Li2O2) has received widespread attention. However, H2O and CO2 in the air can cause some adverse reactions. In particular, the effect of H2O on the discharge and charging process is very complicated, and researchers use pure O2 instead of air to prevent these complex side effects. Therefore, lithium-air batteries are often referred to as lithium oxygen (Li-O2) batteries. Depending on the electrolyte in the battery, Li-O2 batteries are divided into non-aqueous, aqueous, solid-state and hybrid types. The structure of non-aqueous Li-O2 batteries is relatively simple, consisting of a porous cathode, a metallic lithium anode and a non-aqueous electrolyte in the middle. However, before practical application, many challenges need to be overcome, such as poor cycle performance, low power capability, and unsatisfactory rate performance. During the discharge and charging process of the battery, the solid product Li2O2 and its by-products are continuously deposited on the cathode surface and in the pores, hindering the Li + The diffusion path of oxygen and O2 hinders the effective reaction and leads to slow cathode kinetics of lithium-oxygen batteries. Therefore, it is very necessary to design and synthesize efficient oxygen cathode materials to address these problems. Summary of the invention

[0004] The present invention provides a lithium oxygen battery and a preparation method thereof, so as to solve the technical problems of poor cycle performance, low power capacity and unsatisfactory rate performance existing in the existing lithium batteries.

[0005] According to one aspect of the present invention, a lithium-oxygen battery is provided, wherein the lithium-oxygen battery comprises a porous composite oxygen electrode, wherein the porous composite oxygen electrode comprises a ZIF67-AgNWs doped framework material.

[0006] Furthermore, the lithium oxygen battery comprises a porous composite oxygen electrode, a negative electrode, an electrolyte, and a separator sandwiched between the porous composite oxygen electrode and the negative electrode, and the lithium oxygen battery is filled with oxygen or a mixed gas containing oxygen;

[0007] The porous composite oxygen electrode comprises a ZIF67-AgNWs doped skeleton material and a binder, and the porous composite oxygen electrode is provided with internal pores for full or partial filling of oxygen; the negative electrode is a lithium sheet; the electrolyte is an organic electrolyte in which lithium salt is dissolved in an anhydrous ether or ionic liquid solvent; and the diaphragm is a glass fiber diaphragm.

[0008] Furthermore, the doping amount of ZIF67 to AgNWs in the ZIF67-AgNWs doped skeleton material is 1-8:1-4.

[0009] Furthermore, the diameter of the AgNWs in the ZIF67-AgNWs doped framework material is 100-300 nm, and the length is 45-50 μm.

[0010] Furthermore, the mass ratio of the ZIF67-AgNWs doped skeleton material to the binder is 7-9:1-3.

[0011] Furthermore, the lithium salt is LiTFSI.

[0012] Furthermore, the solvent is tetraethylene glycol dimethyl ether (TEGDME).

[0013] Furthermore, the preparation method of the ZIF67-AgNWs doped skeleton material is:

[0014] CoCl2 and polyvinyl pyrrolidone are dispersed in a mixed solution of methanol and DMF, which is used as solution a; 2-methylimidazole is dispersed in a methanol solution as solution b; solution a and solution b are mixed and stirred, 1 mM salicylic acid is added, and ultrasonic treatment is performed to obtain a mixed solution; AgNWs are added dropwise to the above mixed solution with a dropper, stirred, and allowed to stand for more than 24 hours. A silver-purple precipitate is obtained by centrifugation, which is then washed with methanol, ethanol, and deionized water respectively. The obtained precipitate is placed in a vacuum oven and dried to obtain a ZIF67-AgNWS doped skeleton material.

[0015] Furthermore, the method for preparing the porous composite oxygen electrode comprises the following steps:

[0016] (1) mixing the ZIF67-AgNWs doped skeleton material and the binder, stirring evenly to obtain a mixed slurry;

[0017] (2) adding 5 to 10 μl of N-methylpyrrolidone to the obtained mixed slurry for dilution;

[0018] (3) coating the mixed slurry on a stainless steel wire mesh and drying it to obtain the porous composite oxygen electrode.

[0019] Furthermore, in step (3), the drying temperature is 80-90° C. and the drying time is 10-15 hours.

[0020] According to another aspect of the present invention, there is also provided a method for preparing a lithium oxygen battery, the method comprising the following steps:

[0021] (1) In an anhydrous and oxygen-free glove box filled with argon circulation, the negative electrode, the separator and the porous composite oxygen electrode are stacked in sequence in a Swagelok type battery mold, and then an electrolyte is added;

[0022] (2) The glove box is placed in a sealed device, pure oxygen is introduced and allowed to stand for 4 hours to obtain a lithium oxygen battery.

[0023] The present invention has the following beneficial effects:

[0024] (1) In the process of charging and discharging the lithium-oxygen battery without lithium carbonate of the present invention, based on the large specific surface area environment provided by the metal skeleton material doped with ZIF67-AgNWs and the conversion reaction of the lithium-oxygen battery, the metal skeleton material doped with ZIF67-AgNWs is used as the O2 electrode material to provide uniform pores with high specific surface area and an adjustable chemical environment for specific interaction with the guest, thereby causing O2 in the electrode to be enriched at the O2 conversion active site and reduced to O2 - , after electrolyte diffusion and Li + The reactants such as lithium peroxide are deposited between the pores of the ZIF67-AgNWs-doped metal skeleton material, and then decomposed during the OER reaction. Since there is no carbon in the lithium-oxygen battery material, the formation of lithium carbonate is avoided, which leads to greater polarization of the positive electrode surface, thus having the advantages of long cycle and high capacity.

[0025] (2) The present invention uses a porous metal skeleton positive electrode material based on doped silver nanoparticles (ZIF67-AgNWs doped skeleton material) to construct a porous composite oxygen electrode for lithium-oxygen batteries. On the one hand, the conversion reaction mechanism of lithium-oxygen batteries The battery discharge capacity is increased; on the other hand, the porous metal skeleton positive electrode material based on doped silver nanoparticles can not only store lithium ions to contribute capacity, but also use the metal active sites in the pores of the porous metal skeleton to catalyze the formation and decomposition of lithium peroxide, a product of the lithium-oxygen battery, during the charging process, thereby overcoming the poor cycling performance of the lithium-oxygen battery caused by the increased polarization of the positive electrode surface due to the formation of lithium carbonate.

[0026] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0028] Figure 1 is the XRD pattern of the porous composite oxygen electrode prepared in Example 1 of the present invention;

[0029] Figure 2 is a prominent reflection diagram of the ZIF67 single crystal at 2θ=7.7° and 10.8° in Example 1 of the present invention;

[0030] Figure 3 1 is a SEM image (a) of a porous composite oxygen electrode prepared in Example 1 of the present invention and a SEM image (b) of a comparative electrode prepared in Comparative Example 1;

[0031] Figure 4 It is a charge and discharge curve diagram of the battery prepared in Comparative Example 1 of the present invention;

[0032] Figure 5 is a charge and discharge curve diagram of a battery prepared in Example 1 of the present invention;

[0033] Figure 6 is a charge and discharge curve diagram of a battery prepared in Example 2 of the present invention;

[0034] Figure 7 It is a charge and discharge curve diagram of the battery prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0035] The embodiments of the present invention are described in detail below with reference to the accompanying drawings. However, the present invention can be implemented in many different ways as defined and covered below.

[0036] An embodiment of the first aspect of the present invention provides a lithium-oxygen battery, wherein the lithium-oxygen battery comprises a porous composite oxygen electrode, wherein the porous composite oxygen electrode comprises a ZIF67-AgNWs doped skeleton material.

[0037] The lithium oxygen battery of the present invention further comprises a porous composite oxygen electrode, a negative electrode, an electrolyte and a diaphragm sandwiched between the porous composite oxygen electrode and the negative electrode, wherein the lithium oxygen battery is filled with oxygen or a mixed gas containing oxygen (wherein the oxygen content is greater than 0wt%); the porous composite oxygen electrode comprises a ZIF67-AgNWs doped skeleton material and a binder, and the porous composite oxygen electrode is provided with an internal pore for full or partial filling of oxygen; the negative electrode is a lithium sheet; the electrolyte adopts an organic electrolyte in which a lithium salt is dissolved in an anhydrous ether or ionic liquid solvent; and the diaphragm is a glass fiber diaphragm.

[0038] The porous composite oxygen electrode of the present invention is a positive electrode material based on a metal organic framework porous structure (MOFs) doped with silver nanoparticles. The MOFs positive electrode material based on the silver nanoparticles is introduced into a lithium oxygen battery to form a lithium carbonate-free lithium oxygen battery. During the discharge process, the silver nanowire material (AgNWs) serves as a base frame for the growth of ZIF67 with cobalt as the central metal atom. The lattice constant of Ag as the base is greater than that of Co. Co will be stretched, the lattice constant will increase, the atomic arrangement will become sparse, the wave function overlap between atoms will decrease, the energy band will become narrower, the d band center will rise, the adsorption energy will be enhanced, and the Li + The positive electrode material provides active sites for the conversion of O2, so that oxygen is reduced to O2 at the positive electrode. - With Li + The reaction generates lithium superoxide (LiO2), which is further reduced or disproportionated at the solid phase interface, and finally generates lithium peroxide (Li2O2) in the pores of the positive electrode of the battery, so that the positive electrode material provides capacity for the discharge product. Usually, Li2O2 requires an overpotential greater than 1V to decompose, so during the subsequent charging process, the Li2O2 deposited in the pores of the positive electrode passes through Li2O2→LiO2+Li + +e - and LiO2→Li + +e - +O2 decomposes in two processes. The positive electrode of the lithium oxygen battery of the present invention overcomes the defect of poor cycle performance of the lithium oxygen battery caused by the production of by-products such as lithium carbonate. It is an electrochemical energy storage system with great potential and is expected to be applied to electric vehicles and large-scale energy storage in the future.

[0039] In addition, the positive electrode of traditional lithium-oxygen batteries usually includes conductive carbon, metal or metal oxide, which only plays the role of catalyzing the formation and decomposition of the product lithium peroxide. Although these materials can provide high battery capacity, they are very easy to produce by-products such as lithium carbonate, causing an insulating layer to form on the surface of the battery positive electrode, resulting in a gradual increase in battery polarization, which in turn affects the battery cycle performance.

[0040] In the process of charging and discharging the lithium-oxygen battery of the present invention, based on the large specific surface area environment provided by the metal skeleton material doped with ZIF67-AgNWs and the conversion reaction of the lithium-oxygen battery, the metal skeleton material doped with ZIF67-AgNWs is used as the O2 electrode material to provide uniform pores with high specific surface area and an adjustable chemical environment for specific interaction with the guest, thereby causing O2 in the electrode to be enriched at the O2 conversion active site and reduced to O2 - , after electrolyte diffusion and Li + The reactants such as lithium peroxide are deposited between the pores of the ZIF67-AgNWs-doped metal skeleton material, and then decomposed during the OER reaction. Since there is no carbon in the lithium-oxygen battery material, the formation of lithium carbonate is avoided, which leads to greater polarization of the positive electrode surface, thus having the advantages of long cycle and high capacity.

[0041] The present invention uses a porous metal skeleton positive electrode material based on doped silver nanoparticles to construct a porous composite oxygen electrode for lithium-oxygen batteries. On the one hand, the conversion reaction mechanism of lithium-oxygen batteries The battery discharge capacity is increased; on the other hand, the porous metal skeleton positive electrode material based on doped silver nanoparticles can not only store lithium ions to contribute capacity, but also use the metal active sites in the pores of the porous metal skeleton to catalyze the formation and decomposition of lithium peroxide, a product of the lithium-oxygen battery, during the charging process, thereby overcoming the poor cycling performance of the lithium-oxygen battery caused by the increased polarization of the positive electrode surface due to the formation of lithium carbonate.

[0042] The preferred positive electrode material ZIF67 in the present application can regulate the composition and pore structure of MOFs by adjusting the precursor, synthesis conditions, post-modification and other methods, so it has the advantages of adjustable and large number of active sites and high specific surface area, and its charging voltage range is consistent with the charging voltage range of lithium-oxygen batteries. As an oxygen electrode material for lithium-ion lithium-oxygen batteries, it can catalyze the decomposition of reaction products (lithium peroxide, Li2O2) and by-products (Li2CO3) during the charging process of lithium-oxygen batteries.

[0043] The preparation method of the above-mentioned ZIF67-AgNWs doped skeleton material is:

[0044] 0.77 mM CoCl2 and 200 mg polyvinyl pyrrolidone were dispersed in a mixed solution of 10 ml methanol and DMF (N, N-dimethylformamide) (the ratio of methanol to DMF was 4:1) as solution a; 6.40 mM 2-methylimidazole was dispersed in a 10 ml methanol solution as solution b; solution a and solution b were mixed and stirred for 0.5 h, 1 mM salicylic acid was added, and ultrasonic treatment was performed for 5 minutes to obtain a mixed solution; AgNWs with an appropriate molar ratio to ZIF67 were added to the mixed solution with a dropper, stirred for 0.5 h, allowed to stand for more than 24 h, and then heated at 8000 rpm min -1 After centrifugation for 5 minutes, a silver-purple precipitate was obtained, which was then washed three times with methanol, ethanol and deionized water respectively. The obtained precipitate was placed in a vacuum oven and vacuum dried at 80°C for 24 hours to obtain a ZIF67-AgNWS doped framework material.

[0045] The specific mechanism of this application is to prepare the electrocatalyst ZIF67-AgNWs by adjusting the d-band broadening and adding a modulator (salicylic acid) to control the crystal morphology, and obtain a bimetallic catalyst with good ORR and OER performance. It is understood that when the adsorbed single energy level interacts with the continuous energy level, its energy will have a certain broadening, and the broadening represents the interaction strength between the metal d orbital and the adsorbate p orbital. The stronger the interaction, the wider the energy band. When the bandwidth narrows and the Fermi level remains unchanged, the d-band center must rise. The d-band broadening is affected by the surrounding stress effect and the ligand effect. By introducing tensile and compressive stresses, or changing the coordination number and coordination strength, the d-band broadening is changed, thereby adjusting the d-band center position and the adsorption energy.

[0046] The lattice constant of Ag is 4.09, while the lattice constant of cobalt is 2.51. If doping is successful, the lattice constant of Ag as the substrate is greater than that of Co. Co will be stretched, the lattice constant will increase, the atomic arrangement will become sparse, the overlap of wave functions between atoms will decrease, the energy band will become narrower, the d-band center will rise, the adsorption energy will be enhanced, and the reaction between Li+ and O2 will be accelerated. In addition, due to the almost carbon-free cathode environment, it is also effective in reducing the formation of lithium carbonate, thereby improving the reaction kinetics of the battery and enhancing the cycle life. At the same time, the modulator salicylic acid is added to compete with 2-methylimidazole in coordination with metal ions.

[0047] The solvent composition changes the ability of the modulator salicylic acid to adjust the monodispersity and crystal size within a limited range. In addition, DMF (NN-dimethylformamide) can be used as a structure-directing agent to further affect the morphology of the structure through its deprotonation and polarity, resulting in an imperfect metal framework, thereby introducing active sites based on lattice defects in the pores, further improving battery performance.

[0048] In an embodiment of the present invention, the doping amount of ZIF67 to AgNWs in the ZIF67-AgNWs doped skeleton material is 1-8:1-4.

[0049] When the conductive carbon material is completely removed from the battery oxygen electrode, the battery discharge capacity decreases significantly and the cycle stability increases significantly; when the positive electrode content is reduced and the conductive carbon content is increased in the oxygen electrode, the battery discharge capacity increases, but the cycle stability deteriorates. In this application, the molar ratio of the lithium oxygen battery positive electrode material and the silver nanomaterial is 1:4. The porous composite electrode prepared with this molar ratio can obtain a large discharge capacity and have stable cycle performance.

[0050] In the embodiment of the present invention, the diameter of AgNWs in the ZIF67-AgNWs doped skeleton material is 100-300nm, and the length is 45-50μm. Since the particle size of ZIF67 is between 200-400nm, the use of AgNWs material with a coarse nanometer size can make it easier for ZIF67 to grow evenly on the surface of AgNWs.

[0051] In an embodiment of the present invention, the mass ratio of the ZIF67-AgNWs doped skeleton material to the binder is 7-9:1-3, preferably 8:2.

[0052] In an embodiment of the present invention, the lithium salt includes LiTFSI.

[0053] In an embodiment of the present invention, the solvent includes tetraethylene glycol dimethyl ether (TEGDME).

[0054] In an embodiment of the present invention, the diaphragm is a glass fiber membrane.

[0055] In an embodiment of the present invention, the method for preparing the porous composite oxygen electrode comprises the following steps:

[0056] (1) mixing the ZIF67-AgNWs doped skeleton material and the binder, stirring evenly to obtain a mixed slurry;

[0057] (2) adding 5 to 10 μl of N-methylpyrrolidone to the obtained mixed slurry for dilution;

[0058] (3) coating the mixed slurry on a stainless steel wire mesh and drying it to obtain the porous composite oxygen electrode.

[0059] Furthermore, in step (3), the drying temperature is 80-90° C. and the drying time is 10-15 hours.

[0060] According to an embodiment of the second aspect of the present invention, there is also provided a method for preparing a lithium oxygen battery, the method comprising the following steps:

[0061] (1) In an anhydrous and oxygen-free glove box filled with argon circulation, the negative electrode, the separator and the porous composite oxygen electrode are stacked in sequence in a Swagelok type battery mold, and then an electrolyte is added;

[0062] (2) The glove box is placed in a sealed device, pure oxygen (99.9%) is introduced and allowed to stand for 4 hours to obtain a lithium oxygen battery.

[0063] The following examples describe the present disclosure in more detail, and these examples are intended for illustrative purposes only.

[0064] Example 1

[0065] This embodiment provides a lithium oxygen battery, comprising a porous composite oxygen electrode, a negative electrode, an electrolyte, and a separator sandwiched between the porous composite oxygen electrode and the negative electrode, wherein the lithium oxygen battery is filled with oxygen or a mixed gas containing oxygen (wherein the oxygen content is greater than 0wt%);

[0066] Preparation method of ZIF67-AgNWS doped skeleton material: 0.77mM CoCl2 and 200mg polyvinyl pyrrolidone were dispersed in 10ml of a mixed solution of methanol and DMF (the ratio of methanol to DMF was 4:1) as solution a; 6.40mM 2-methylimidazole was dispersed in 10ml of methanol solution as solution b; solution a and solution b were mixed and stirred for 0.5h, then 1mM salicylic acid was added and ultrasonicated for 5 minutes. 3.08mM AgNWs was added to the mixed solution of solution a and solution b with a dropper, stirred for 0.5h, left to stand for more than 24h, and heated at 8000rpm min -1 After centrifugation for 5 minutes, a silver-purple precipitate was obtained, which was then washed three times with methanol, ethanol and deionized water respectively. The obtained precipitate was placed in a vacuum oven and vacuum dried at 80°C for 24 hours to obtain a ZIF67-AgNWS doped framework material.

[0067] The porous composite oxygen electrode comprises a ZIF67-AgNWs doped skeleton material and a polyvinylidene fluoride binder, and the porous composite oxygen electrode is provided with internal channels for full or partial filling of oxygen; the negative electrode is a lithium sheet; the electrolyte is an organic electrolyte in which lithium salt is dissolved in an anhydrous ether or ionic liquid solvent; and the diaphragm is a glass fiber diaphragm.

[0068] The molar mass ratio of ZIF-67 to AgNWs in the ZIF67-AgNWs doped framework material is 1:4, and the mass ratio of the ZIF67-AgNWs doped framework material to the binder is 8:2.

[0069] The preparation method of the porous composite oxygen electrode comprises:

[0070] (1) mixing the ZIF67-AgNWs doped skeleton material and the polyvinylidene fluoride binder in a ratio of 8:2 and stirring for 12 hours to obtain a mixed slurry;

[0071] (2) adding 5 μl of N-methylpyrrolidone solvent to the obtained mixed slurry for dilution;

[0072] (3) The mixed slurry was coated on a stainless steel mesh and dried at 80°C for 15 h to obtain a porous composite oxygen electrode. The loading mass on the porous composite oxygen electrode was 0.6 mg cm -2 .

[0073] The preparation method of the lithium oxygen battery is as follows: a porous composite oxygen electrode, a metal lithium negative electrode, and 1M LiTFSI are dissolved in an electrolyte of tetraethylene glycol dimethyl ether, and a glass fiber separator is sandwiched between the porous composite oxygen electrode and the negative electrode; a sealed metal battery barrel is used to assemble the battery in an argon glove box, and the battery is allowed to stand at room temperature for 4 hours after assembly.

[0074] Example 2

[0075] The present embodiment provides a lithium oxygen battery, comprising a porous composite oxygen electrode, a negative electrode, an electrolyte, and a separator sandwiched between the porous composite oxygen electrode and the negative electrode, wherein the lithium oxygen battery is filled with oxygen or a mixed gas containing oxygen (wherein the oxygen content is greater than 0wt%); the porous composite oxygen electrode comprises a ZIF67-AgNWs doped skeleton material and a polyvinylidene fluoride binder, and the porous composite oxygen electrode is provided with an internal pore for full or partial filling of oxygen; the negative electrode is a lithium sheet; the electrolyte is an organic electrolyte in which a lithium salt is dissolved in an anhydrous ether or ionic liquid solvent; and the separator is a glass fiber separator.

[0076] Preparation method of ZIF67-AgNWS doped skeleton material: 0.77mM CoCl2 and 200mg polyvinyl pyrrolidone were dispersed in 10ml of a mixed solution of methanol and DMF (the ratio of methanol to DMF was 4:1) as solution a; 6.40mM 2-methylimidazole was dispersed in 10ml of methanol solution as solution b; solution a and solution b were mixed and stirred for 0.5h, then 1mM salicylic acid was added and ultrasonicated for 5 minutes. 0.1mM AgNWs was added to the mixed solution of solution a and solution b with a dropper, stirred for 0.5h, left to stand for more than 24h, and heated at 8000rpm min -1After centrifugation for 5 minutes, a silver-purple precipitate was obtained, which was then washed three times with methanol, ethanol and deionized water respectively. The obtained precipitate was placed in a vacuum oven and vacuum dried at 80°C for 24 hours to obtain a ZIF67-AgNWS doped framework material.

[0077] The molar mass ratio of ZIF-67 to AgNWS in the ZIF67-AgNWs doped framework material is 8:1, and the mass ratio of the ZIF67-AgNWs doped framework material to the binder is 8:2.

[0078] The preparation method of the porous composite oxygen electrode comprises:

[0079] (1) mixing the ZIF67-AgNWs doped skeleton material and the polyvinylidene fluoride binder in a ratio of 8:2 and stirring for 12 hours to obtain a mixed slurry;

[0080] (2) adding 10 μl of N-methylpyrrolidone solvent to the obtained mixed slurry for dilution;

[0081] (3) The mixed slurry was coated on a stainless steel mesh and dried at 80°C for 15 h to obtain a porous composite oxygen electrode. The loading mass on the porous composite oxygen electrode was 0.6 mg cm -2 .

[0082] The preparation method of the lithium oxygen battery is as follows: a porous composite oxygen electrode, a metal lithium negative electrode, and 1M LiTFSI are dissolved in an electrolyte of tetraethylene glycol dimethyl ether, and a glass fiber separator is sandwiched between the porous composite oxygen electrode and the negative electrode; a sealed metal battery barrel is used to assemble the battery in an argon glove box, and the battery is allowed to stand at room temperature for 4 hours after assembly.

[0083] Example 3

[0084] The present embodiment provides a lithium oxygen battery, comprising a porous composite oxygen electrode, a negative electrode, an electrolyte, and a separator sandwiched between the porous composite oxygen electrode and the negative electrode, wherein the lithium oxygen battery is filled with oxygen or a mixed gas containing oxygen (wherein the oxygen content is greater than 0wt%); the porous composite oxygen electrode comprises a ZIF67-AgNWs doped skeleton material and a polyvinylidene fluoride binder, and the porous composite oxygen electrode is provided with an internal pore for full or partial filling of oxygen; the negative electrode is a lithium sheet; the electrolyte is an organic electrolyte in which a lithium salt is dissolved in an anhydrous ether or ionic liquid solvent; and the separator is a glass fiber separator.

[0085] Preparation method of ZIF67-AgNWS doped skeleton material: 0.77mM CoCl2 and 200mg polyvinyl pyrrolidone were dispersed in 10ml of a mixed solution of methanol and DMF (the ratio of methanol to DMF was 4:1) as solution a; 6.40mM 2-methylimidazole was dispersed in 10ml of methanol solution as solution b; solution a and solution b were mixed and stirred for 0.5h, then 1mM salicylic acid was added and ultrasonicated for 5 minutes. 0.19mM AgNWs was added to the mixed solution of solution a and solution b with a dropper, stirred for 0.5h, left to stand for more than 24h, and heated at 8000rpm min -1 After centrifugation for 5 minutes, a silver-purple precipitate was obtained, which was then washed three times with methanol, ethanol and deionized water respectively. The obtained precipitate was placed in a vacuum oven and vacuum dried at 80°C for 24 hours to obtain a ZIF67-AgNWS doped framework material.

[0086] The molar mass ratio of ZIF-67 to AgNWS in the ZIF67-AgNWs doped framework material is 4:1, and the mass ratio of the ZIF67-AgNWs doped framework material to the binder is 8:2.

[0087] The preparation method of the porous composite oxygen electrode comprises:

[0088] (1) mixing the ZIF67-AgNWs doped framework material and the polyvinylidene fluoride binder in a ratio of 8:2 and stirring for 12 hours to obtain a mixed slurry;

[0089] (2) adding 8 μl of N-methylpyrrolidone solvent to the obtained mixed slurry for dilution;

[0090] (3) The mixed slurry was coated on a stainless steel mesh and dried at 80°C for 15 h to obtain a porous composite oxygen electrode. The loading mass on the porous composite oxygen electrode was 0.6 mg cm -2 .

[0091] The preparation method of the lithium oxygen battery is as follows: a porous composite oxygen electrode, a metal lithium negative electrode, and 1M LiTFSI are dissolved in an electrolyte of tetraethylene glycol dimethyl ether, and a glass fiber separator is sandwiched between the porous composite oxygen electrode and the negative electrode; a sealed metal battery barrel is used to assemble the battery in an argon glove box, and the battery is allowed to stand at room temperature for 4 hours after assembly.

[0092] Comparative Example 1

[0093] The difference between this comparative example and Example 1 is that the comparative electrode includes conductive carbon and polyvinylidene fluoride binder, and the mass ratio of the conductive carbon to the polyvinylidene fluoride binder is 8:2.

[0094] The preparation method of the electrode comprises:

[0095] The conductive carbon was ground in a mortar for more than 30 minutes. The ground conductive carbon was placed in a vial, and polyvinylidene fluoride binder and N-methylpyrrolidone solvent were added and stirred for 12 hours to obtain a mixed slurry. The slurry was coated on a 3000 mesh stainless steel mesh, dried in an oven at 80°C for 15 hours, and then taken out as a comparison electrode. The load mass on the electrode sheet was 0.6 mg / cm -2 .

[0096] The lithium oxygen battery includes the comparative electrode of comparative example 1, a metallic lithium negative electrode, an electrolyte in which 1M LiTFSi is dissolved in tetraethylene glycol dimethyl ether, and a glass fiber separator; the battery is assembled in an argon glove box using a sealed metal battery barrel and allowed to stand at room temperature for 4 hours after assembly.

[0097] The performance of the lithium oxygen batteries prepared in Examples 1-3 and Comparative Example 1 was analyzed, and the results were as follows:

[0098] 1. Phase analysis of electrodes

[0099] Due to the complexity of the phase of the ZIF67-AgNWs doped skeleton material, the simulated X-ray diffraction pattern can be used to analyze the phase and crystallinity of the positive electrode material.

[0100] Figure 1 This is the X-ray diffraction pattern of the porous composite oxygen electrode of Example 1.

[0101] from Figure 1 (a) shows the diffraction peak position in the porous composite oxygen electrode ( Figure 1 (a)) and simulation diagram ( Figure 1 (b)) are in good agreement, indicating that they are all pure-phase ZIF67 with high crystallinity. Figure 2 The prominent reflections of the ZIF67 single crystal at 2θ=7.7° and 10.8° correspond to the

[210] and

[300] planes, respectively. This indicates that the ZIF67-AgNWs doped framework material in the porous composite oxygen electrode prepared in Example 1 has not changed during the grinding preparation, so that normal catalytic reactions can be carried out in the battery.

[0102] 2. Electrode morphology analysis

[0103] Figure 3 (a) is a SEM image of the porous composite oxygen electrode of Example 1. From the figure, it can be seen that the cubic ZIF67 doped silver nanomaterial positive electrode particles with a diameter of about 200 to 400 nm have internal pores that are significantly larger than the pores of the comparison electrode, which can accommodate more product Li2O2.

[0104] Figure 3(b) is a SEM image of the comparative electrode of Example 1, in which the conductive carbon is nanoparticles of about 50 nm.

[0105] 3. Analysis of electrical properties of electrodes

[0106] Figure 4 This is the charge and discharge cycle curve of the comparative lithium oxygen battery using conductive carbon as the porous oxygen electrode in Example 1. The first cycle capacity reaches 513 mAh g -1 However, in the second cycle of discharge, the discharge capacity dropped to 420mAh g-1. After 10 cycles of the battery, the capacity retention rate was less than 60%. This is because the discharge product Li2O2 and the intermediate product of the lithium-oxygen reaction have strong oxidizing properties. A large amount of by-products such as Li2CO3 are formed during the charge and discharge process, covering the active sites on the surface of the oxygen electrode. Due to the limited catalytic effect of conductive carbon on the products and by-products, the product lithium peroxide and the by-product lithium carbonate in the charging stage cannot be completely decomposed, and the decomposition is incomplete, resulting in a reduction in the active sites of the products in subsequent cycles, causing the battery cycle life to decay rapidly.

[0107] Figure 6 and Figure 7 Embodiment 2 and embodiment 3 are charge and discharge cycle curves of lithium oxygen batteries based on different molar ratios of ZIF67 and AgNWs in the positive electrode material ZIF67-AgNWs doped skeleton material.

[0108] From Example 2 ( Figure 6 ) It can be seen that due to the almost non-conductivity of the ZIF67-AgNWs doped skeleton material in the positive electrode and the high molar ratio of ZIF67 to AgNWs, a suspected interface layer problem occurs in the positive electrode, and a good conductive network is not formed, and the advantages of the ZIF67-AgNWs doped skeleton material cannot be brought into play.

[0109] Example 3 Figure 7 ) It can be seen that after further adjusting the molar ratio of MOFs and silver nanomaterials and relatively reducing the proportion of ZIF67 in the entire material, the battery performance has been improved to a certain extent.

[0110] According to Example 1 ( Figure 5 ) It can be seen that the charging platform of the silver-doped ZIF67 lithium-oxygen battery is significantly lower than that of the comparative lithium-oxygen battery in Comparative Example 1. The discharge capacity of the battery is improved by a certain amount compared with Comparative Example 1, and the battery cycle performance is improved, and the polarization is greatly reduced. It can be seen that the porous composite oxygen electrode prepared in Example 1 not only reduces the high polarization of the carbon-containing lithium-oxygen battery but also still has the high capacity characteristics of the lithium-oxygen battery.

[0111] In summary, in lithium carbonate-free lithium oxygen batteries, the discharge capacity is the discharge capacity of the lithium-oxygen reaction, and the product lithium peroxide and by-products can be completely decomposed during the charging process. This is why the cycle performance of lithium carbonate-free lithium oxygen hybrid batteries is more stable than that of carbon-containing lithium oxygen batteries.

[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium oxygen battery, characterized in that: The lithium-oxygen battery comprises a porous composite oxygen electrode, wherein the porous composite oxygen electrode comprises a ZIF67-AgNWs doped framework material.

2. The lithium oxygen battery according to claim 1, characterized in that: The lithium oxygen battery also includes a negative electrode, an electrolyte, and a separator sandwiched between the porous composite oxygen electrode and the negative electrode, and the lithium oxygen battery is filled with oxygen or a mixed gas containing oxygen; The porous composite oxygen electrode comprises a ZIF67-AgNWs doped skeleton material and a binder, and the ZIF67-AgNWs doped skeleton material is provided with internal pores for full or partial filling of oxygen; the negative electrode is a lithium sheet; the electrolyte is an organic electrolyte in which a lithium salt is dissolved in an anhydrous ether or ionic liquid solvent.

3. The lithium oxygen battery according to claim 1, characterized in that The doping amount of ZIF67 to AgNWs in the ZIF67-AgNWs doped framework material is 1-8:1-4.

4. The lithium oxygen battery according to claim 1, characterized in that: The diameter of the AgNWs in the ZIF67-AgNWs doped framework material is 100-300 nm, and the length is 45-50 μm.

5. The lithium oxygen battery according to claim 2, characterized in that: The mass ratio of the ZIF67-AgNWs doped skeleton material to the binder is 7-9:1-3.

6. The lithium oxygen battery according to claim 2, characterized in that: The lithium salt is LiTFSI.

7. The lithium oxygen battery according to claim 2, characterized in that: The solvent is tetraethylene glycol dimethyl ether.

8. The lithium oxygen battery according to claim 1 or 2, characterized in that: The preparation method of the ZIF67-AgNWs doped skeleton material is: Dispersing CoCl2 and polyvinyl pyrrolidone in a mixed solution of methanol and DMF is used as a solution; Dispersing 2-methylimidazole in a methanol solution as solution b; mixing solution a and solution b, adding salicylic acid, and performing ultrasonic treatment to obtain a mixed solution; AgNWs were added dropwise to the mixed solution with a dropper, stirred, and allowed to stand for more than 24 hours. A silver-purple precipitate was obtained by centrifugation, which was then washed with methanol, ethanol, and deionized water, respectively. The obtained precipitate was dried in a vacuum oven to obtain a ZIF67-AgNWS doped framework material.

9. The lithium oxygen battery according to claim 2, characterized in that: The method for preparing the porous composite oxygen electrode comprises the following steps: (1) mixing the ZIF67-AgNWs doped skeleton material and the binder, stirring evenly to obtain a mixed slurry; (2) adding 5 to 10 μl of N-methylpyrrolidone to the obtained mixed slurry for dilution; (3) coating the mixed slurry on a stainless steel wire mesh and drying it to obtain the porous composite oxygen electrode.

10. A method for preparing a lithium oxygen battery, characterized in that: The method comprises the following steps: (1) In an anhydrous and oxygen-free glove box filled with argon circulation, the negative electrode, the separator and the porous composite oxygen electrode described in claim 2 are stacked in sequence in a Swagelok-type battery mold, and then an electrolyte is added; (2) The glove box is placed in a sealed device, pure oxygen is introduced and allowed to stand for 4 hours to obtain a lithium oxygen battery.